Analytical study on reinforced concrete frames subject to compressive arch action. (15th June 2017) - Kang, Shao-Bo; Tan, Kang Hai
Highlights: An analytical model is proposed for predicting the compressive arch action of reinforced concrete frames. A rigid-plastic model is derived to evaluate the horizontal and rotational stiffness of columns. Shear force in the beam-column joint and bending moment at the joint face are assessed through the analytical model. Abstract: Reinforced concrete beams can resist applied vertical loads through the development of compressive arch action (CAA) when adequate horizontal restraints are provided at the ends. However, at the frame level, CAA tends to push adjoining columns outwards and may induce premature flexural or shear failure to the columns. Therefore, under CAA, flexural and shear resistances of the connecting columns need to be examined. This paper describes an analytical study on the behaviour of reinforced concrete frames subject to CAA. In the study, lateral and rotational stiffness of reinforced concrete columns is determined based on a rigid-plastic assumption. CAA of reinforced concrete frames is investigated through an analytical model, in which deformations of columns are taken into consideration. Besides, shear force and bending moment in the column are calculated from equilibrium to shed light on the possible failure mode of columns under CAA. Parametric studies are also conducted to investigate the dominant parameters on the behaviour of columns. Finally, recommendations are provided for the design of reinforced concrete columns against CAA in the connecting beam.